(untitled) (Simbiótica. Revista Eletrônica, 2022)
In the word`s cut, the overture. We have followed with landscapes, images, writings in surfaces. Its graphic circumstances – unsustainable forms of other hearings – address the elusive and dissonant in gesture and thought. Here (in this article) we rehearse some improbable approaches between them trying to experience another way of narrating. Keywords: Landscapes; Images; Writings; Surfaces.